Improvements in the prediction of the wave making resistance from potential flow by using transverse wave cut methods - Will, Johannes; Kömpe, Anja (Volume 2: CFD and VIV, 2015)
The reliable and correct determination of the wave resistance is the key to an efficient ship design, as the wave resistance is one on the major factors concerning building and operational costs. In this paper the authors present a new approach to transverse wave cut analysis to overcome the major shortcoming of the resistance prediction from potential flow: a numerically stable and physically sound estimate for the magnitude of the wave making resistance.